Ancient frameworks as modern templates: exploring reef rubble consolidation in an ancient reef system - Godbold, Amanda; James, Chase C.; Kießling, Wolfgang; Hohmann, Niklas; Jarochowska, Emilia; Corsetti, Frank A.; Bottjer, David J. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2025)
Both natural and human-induced stressors cause reef erosion, resulting in reef rubble formation. When consolidated, the rubble can facilitate reef recovery, sparking interest in artificial rubble stabilization as a method for reef restoration. However, our understanding of the natural processes governing coral reef regeneration within rubble beds is limited. This study examines the regeneration processes within ancient rubble frameworks in a Late Triassic carbonate platform. Results show that Late Triassic rubble environments exhibit successional trajectories similar to contemporary rubble environments. Key organisms such as sponges, calcareous red algae, bryozoans, microbes and scleractinian corals, which are instrumental in the consolidation of modern reef rubble, appear to have played comparable roles during the Late Triassic. The similarities between Late Triassic and modern reef rubble consolidation highlight enduring ecological mechanisms important for reef regeneration. This study deepens our understanding of reef dynamics and offers valuable insights for improving current reef restoration strategies, grounded in time-tested natural processes.
CRIS-Team Scopus Importer:2025-02-21
Keywords: breccia; Late Triassic; reef; reef regeneration; reef rubble